Mild multiple sclerosis challenges shape work experiences, affect self-concept, and are often trivialized despite disclosure - Grytvik Hartvedt, Maria; Normann, Britt; Sivertsen, Marianne; Arntzen, Ellen Christin (Frontiers in Rehabilitation Sciences, 2025)
IntroductionDespite mild disability, people with multiple sclerosis (PwMS) often face work-related challenges and reduced employment. Their experiences regarding work challenges are understudied.PurposeTo explore experienced work challenges and possibilities for sustained employment among employed PwMS with mild to moderate disability.Materials and methodsIn-depth interviews with 26 employed PwMS analyzed using systematic text condensation guided by Goffman's theories on self and social interaction.ResultsThree categories were developed: (1) unspoken work challenges, (2) the cumulative impact of mild MS symptoms on work challenges, and (3) disability and work challenges influence “who I am at work”. Communication about work challenges was often limited even when MS was disclosed. Most participants experienced difficulties related to cumulation and interplay of symptoms and work challenges, resulting in reduced work capacity, hours and negative thoughts about themselves, confidence and perceived prospects for job retention. Feeling capable in handling work tasks were believed to facilitate sustained employment.ConclusionMildly disabled PwMS often trivialized and avoided addressing work challenges to maintain self-concept, social order and role at work, even after MS was disclosed. Recognizing and addressing mild symptoms and work challenges while maintaining self-concept, sense of capability and acceptance at work, may facilitate sustained employment.